Newborn pulse oximetry screening in the context of a high antenatal detection rate of critical congenital heart disease - Cloete, Elza (Acta Paediatr, 2019)
AIM: Assess the potential additional benefit from pulse oximetry screening in the early detection of critical congenital heart disease in a country with a well‐developed antenatal ultrasound screening programme. METHODS: Live‐born infants, pregnancy terminations and stillbirths from 20 weeks’ gestational age, between 2013 and 2015, with critical cardiac defects defined as primary or secondary targets of pulse oximetry screening were identified. Critical defects were those resulting in the death of a fetus or an infant in the first 28 days after birth, or a defect requiring intervention in the first 28 days. RESULTS: Two hundred and sixty‐eight infants and Fetuses were identified. Antenatal detection rates improved from 69% to 77% over the study period. An associated co‐morbidity improved antenatal detection rates. Twenty‐seven live‐born infants were diagnosed after discharge: 15 aortic arch obstruction (AAO); 10 d‐loop transposition of the great arteries (d‐TGA), and two total anomalous pulmonary venous drainage (TAPVD). Of these, five with AAO, nine with d‐TGA and likely both with TAPVD could potentially have been detected with oximetry screening. CONCLUSION: The antenatal detection of critical cardiac anomalies continues to improve in New Zealand. Despite high antenatal detection rates for most lesions, universal postnatal oximetry screening has the potential to improve early detection.